A Practical Guide to the Safety and Monitoring of New IBD Therapies. Issue 5 (12th October 2018) - Click, Benjamin; Regueiro, Miguel
Abstract: The therapeutic armamentarium of inflammatory bowel disease is rapidly evolving with the development of novel treatment options including targeted monoclonal antibodies and small molecules. With these new therapies come additional safety and side effect concerns. Infections, malignancies, immunogenicity, and metabolic issues exist for each treatment. Management of these agents in the face of such complications is a challenge clinicians will encounter. In this article, we review the existing safety data behind the monoclonal antibodies and small molecules, suggest appropriate risk stratification and assessment considerations before and during therapy, and make expert recommendations on the management of potential complications or clinical scenarios.